Estudo e proposta de um curso sobre doação e transplante de órgãos no ambiente virtual de aprendizagem moodle - Westin, Ursula Marcondes (2013)
The organ donation and transplantation have been a much discussed topic worldwide because of the great advances that medicine has made in recent years. However, even relevant, this topic still generates controversy and discomfort because most of the population, including many health students have a insufficient knowledge about laws which govern the process of donation and transplantation in Brazil, as well as basic issues but fundamental on the subject. The aim of this study is to development a prototype of a distance learning course, so that students in the health field may have the opportunity to learn about organ donation and transplantation, since the topic is hardly offered during graduation in most of Brazilian Universities. We picked up for the creation of a online course prototype because the internet being currently too much strong to teaching and search. The Distance Education together the internet became as an effective tool in the teaching-learning students, breaking down barriers imposed by time and distance. The literature review in the area, the analysis of the politicalpedagogical projects of health courses, as well as the information available on the Internet and the knowledge of the 150 fourth graders of the Federal University of São Carlos through a structured questionnaire served as support for the creation of the prototype. The data obtained from the questionnaire were coded, organized and analyzed quantitatively using descriptive statistics by the Statistical Package for Social Sciences (SPSS ®). The results show that it is essential to approach the subject during the graduation training of future professionals capable of changing reality of the country about the process of organ donation and transplantation.